A green approach toward epoxy-benzoxazine copolymers with shape-memory ability - R. Ambrozic; A. Rucigaj; M. Krajnc (eXPRESS Polymer Letters)
In the frame of green-based chemistry, advanced shape memory polymers are designed from benzoxazine (RSBOX) and epoxy (R-EP) resins basing on potential natural raw materials, such as resorcinol and stearylamine. Thermal curing, investigated by differential scanning calorimetry, shows several overlapping peaks suggesting a complex curing mechanism. Dynamic mechanical analysis of cured RS-BOX/R-EP copolymers demonstrates an increase in the glass temperature and narrower glass transition by the increase of the RS-BOX ratio. In contrast, crosslinking density increases with higher epoxy resin content. All investigated materials possess one-way dual shape memory ability triggered by glass transition temperature with excellent shape fixity, while the shape recovery values ranged between 95 and 100%. The duration of the recovery process is significantly influenced by the RS-BOX amount. Additionally, the mechanical and shape memory properties of fully bio-based SMPs might be suitably tailored for advanced applications by merely varying the initial composition.